Mastering the Zone : The Next Step in Achieving Superhealth and Permanent Fat Loss - Sears, Barry, 1947- (New York Regan Books, 1997)
Arguing that eating fatty foods does not make a person fat, the author provides more than two hundred recipes, accompanied by dietary strategies and guidelines on working with the Zone weight loss program
Include Reference and Index
Keywords: Weight loss -- Nutrition -- Health